2014
DOI: 10.1175/mwr-d-13-00401.1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Antarctic Observational Network with the Antarctic Mesoscale Prediction System (AMPS)

Abstract: Station siting for environmental observing networks is usually made subjectively, which suggests that the monitoring goals for the network may not be met optimally or cost effectively. In Antarctica, where harsh weather conditions make it difficult to install and maintain stations, practical considerations have largely guided the development of the staffed and automated weather station network. The current network coverage in Antarctica is evaluated as a precursor to optimal network design. The Antarctic Mesos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(28 citation statements)
references
References 25 publications
4
24
0
Order By: Relevance
“…Furthermore, most relevant to the applicability of network design, the pointwise statistics of the AMPS output and observations have been shown to be comparable. For example, as a precursor to this study, Bumbaco et al (2014) found good agreement for point correlations between station observations and AMPS output (both the analyses and forecasts) for 2-m temperature and surface pressure, lending confidence that AMPS output can be used for optimal network design. Here, we use 2-m air temperature field output from the 15-km AMPS grid over the period 31 September 2008-1 October 2012.…”
Section: A Antarctic Mesoscale Prediction Systemmentioning
confidence: 57%
See 3 more Smart Citations
“…Furthermore, most relevant to the applicability of network design, the pointwise statistics of the AMPS output and observations have been shown to be comparable. For example, as a precursor to this study, Bumbaco et al (2014) found good agreement for point correlations between station observations and AMPS output (both the analyses and forecasts) for 2-m temperature and surface pressure, lending confidence that AMPS output can be used for optimal network design. Here, we use 2-m air temperature field output from the 15-km AMPS grid over the period 31 September 2008-1 October 2012.…”
Section: A Antarctic Mesoscale Prediction Systemmentioning
confidence: 57%
“…While the network is important for furthering these goals, both existing and potential new stations may also be valuable for the analysis of specific phenomena, forecasting for a specific area of operations, or various other monitoring purposes. We consider the locations of weather stations that are assimilated into WRF as defined in Bumbaco et al (2014). Namely, we use the locations of the weather stations that reported temperature (i) on at least 90% of the days (defined as ''CD90'' stations for 90% ''complete data'') and (ii) on at least 75% of the days (defined as ''CD75'' stations for 75% ''complete data'') over the 2008-12 period.…”
Section: B Antarctic Surface Observing Networkmentioning
confidence: 99%
See 2 more Smart Citations
“…Dee et al, 2011;Murphy et al, 2014;Driemel et al, 2016). These observations could also play a critical role in modern NWP systems, especially at high latitudes where in-situ observations are rare (e.g., Bumbaco et al, 2014). However, benefits from assimilation of radiosonde and wind profiler data have been detected also for short-range forecasts for Central Europe (Federico, 2013), and studies on temperature and humidity retrievals from satellite and ground-based microwave radiometers and their assimilation into NWP system have also been made (e.g., Knupp et al, 2009;Guedj et al, 2010;Caumont et al, 2016).…”
Section: Introductionmentioning
confidence: 99%